EMPATI DAN PERAN BYSTANDER DALAM CYBERBULLYING: FAMILY COMMUNICATION PATTERN SEBAGAI MEDIATOR - Charyna Ayu Rizkyanti; Asti Hesti Cahyani; Salfira Salsabilla; Asti Aulia (Jurnal Psikohumanika, 2021)
Since social media have become deeply enmeshed in adolescents’ everyday lives particularly during the stay at home condition of Pandemic Covid-19, research concern about the effects of bystander in cyberbullying is growing. The purpose of this study was to determine the mediator roles of parent communication pattern in the effect of empathy on cyberbystander among adolescents social media users. A total 447 adolescents aged 12-21 years were involved and completed cyberbullying bystander scale (CBS) by Sarmiento et al., (2019), The Basic Empathy Scale (BES) by Jolliffe & Farrington (2006), and The Revised Family Communication Pattern (RFCP) by Koerner & Fitzpatrick (2002). The results revealed the parent communnication pattern partially mediated the effect of empathy towards cyberbystander behaviour (B = 0,0241, LLCI = 0,0096, ULCI = 0,0403). It emphasizes empathy has a strong direct effect on cyberbystander behavior. Our findings uderline the importance of the family functioning to strengthening the adolescents empathy to avoid them of being cyberbystander.